Effects of light regimes on circadian gene co‐expression networks in Arabidopsis thaliana - Quentin Rivière; Virginie Raskin; Romário deMelo; Stéphanie Boutet; Massimiliano Corso; Matthieu Defrance; Alex A. R. Webb; Nathalie Verbruggen; Armand D. Anoman (Plant Direct)
Abstract Light/dark (LD) cycles are responsible for oscillations in gene expression, which modulate several aspects of plant physiology. Those oscillations can persist under constant conditions due to regulation by the circadian oscillator. The response of the transcriptome to light regimes is dynamic and allows plants to adapt rapidly to changing environmental conditions. We compared the transcriptome of Arabidopsis under LD and constant light (LL) for 3 days and identified different gene co‐expression networks in the two light regimes. Our studies yielded unforeseen insights into circadian regulation. Intuitively, we anticipated that gene clusters regulated by the circadian oscillator would display oscillations under LD cycles. However, we found transcripts encoding components of the flavonoid metabolism pathway that were rhythmic in LL but not in LD. We also discovered that the expressions of many stress‐related genes were significantly increased during the dark period in LD relative to the subjective night in LL, whereas the expression of these genes in the light period was similar. The nocturnal pattern of these stress‐related gene expressions suggested a form of “skotoprotection.” The transcriptomics data were made available in a web application named Cyclath, which we believe will be a useful tool to contribute to a better understanding of the impact of light regimes on plants.